The Development of Interactive Audio-Visual-Based Media Using VideoScribe to Reduce Misconceptions Electrical Potential and ECG Material - Sihombing, Rizky Agassy; Muslim, Muslim; Rahman, Taufik (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2023)
This research aimed to assess the suitability of the developed Audio-Visual Media and its effectiveness in reducing student misconceptions. The research follows the R&D (Research and Development) approach, specifically utilizing the ADDIE development model developed by Branch. The research participants comprised 17 9th-grade students from SMP Swasta Hang Tuah 2 Medan. The research procedures included a pre-survey, instrument creation, survey and observation, and validation. The results of the developed media showed that the first indicator, related to the response to material presentation, fell within the